Synthesis and Characterization of Wall Paint Based on Red Beetroot Betacyanin Pigment with Maceration - Dendy Randa; Upik Nurbaiti; Fianti; Budi Astuti; Agus Yulianto (Jurnal Fisika, 2025)
Every year, the paint industry in Indonesia continues to grow. This is due to the growth of the property and housing sectors, which increases the demand for paint nationwide. This research aims to develop environmentally friendly wall paint using betacyanin pigment from red beet tubers through a maceration process as an alternative paint color that is sustainable and beneficial for health and the environment. Betacyanin pigment extraction was carried out using the maceration method with 96% ethanol for 48 hours, then filtered using filter paper and evaporated. Binder and pigment are mixed in a ratio of 14.3:2, 14.3:5, 14.3:8, 14.3:11, 14.3:14, and 14.3:17 until homogeneous. Paint characterization is done through pH, color, density, and adhesion tests. The research results show that the sixth paint variation, with a binder and pigment composition ratio of 14.3 ml:17 ml, provides the most optimal results that closely align with SNI. The paint has a deep red color, pH 7.6, density of 1.18 g/cm³, and adhesion of 100%.